2015
DOI: 10.1098/rspb.2015.0320
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid behavioural rule of adaptation and drift explains the emergent architecture of antagonistic networks

Abstract: Ecological processes that can realistically account for network architectures are central to our understanding of how species assemble and function in ecosystems. Consumer species are constantly selecting and adjusting which resource species are to be exploited in an antagonistic network. Here we incorporate a hybrid behavioural rule of adaptive interaction switching and random drift into a bipartite network model. Predictions are insensitive to the model parameters and the initial network structures, and agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 61 publications
2
36
0
Order By: Relevance
“…This is often a simplifying assumption, as adaptive foraging (see review in Valdovinos et al 2010) or other forms of adaptive behaviour in response, e.g., to environmental changes (Strona and Lafferty 2016) can often cause links to form, change in strength, or disappear as time progresses. Adaptive networks has been shown to reproduce realistic food-web structures (Nuwagaba et al 2015), to promote stability (Nuwagaba et al 2017), and to allow for positive complexity-stability relationships. For example, Kondoh (2003) and Kondoh (2006) showed that foraging adaptation enhances stability of trophic communities.…”
Section: Trait-mediated Interactions and Adaptive Network: Food Websmentioning
confidence: 99%
“…This is often a simplifying assumption, as adaptive foraging (see review in Valdovinos et al 2010) or other forms of adaptive behaviour in response, e.g., to environmental changes (Strona and Lafferty 2016) can often cause links to form, change in strength, or disappear as time progresses. Adaptive networks has been shown to reproduce realistic food-web structures (Nuwagaba et al 2015), to promote stability (Nuwagaba et al 2017), and to allow for positive complexity-stability relationships. For example, Kondoh (2003) and Kondoh (2006) showed that foraging adaptation enhances stability of trophic communities.…”
Section: Trait-mediated Interactions and Adaptive Network: Food Websmentioning
confidence: 99%
“…Some recent assembly-level models further allow limited evolutionary processes (e.g. Drossel et al 2001;McKane 2004) and adaptive response to disturbance (Kondoh 2003;Zhang et al 2011;Suweis et al 2013;Nuwagaba et al 2015;Minoarivelo and Hui 2016;Hui et al 2015). In particular, the model proposed by Loeuille and Loreau (2005) can depict the emergence of complex food webs through ecological and evolutionary processes involving trait-mediated interactions.…”
Section: Invasion Fitnessmentioning
confidence: 99%
“…More recently, it has been recognised that species assemblages in unsaturated local communities are at least in part driven by neutral forcing via the continuous influx of regional and alien species (Hubbell 2001;Stohlgren et al 2003). Despite contrasting opinions on the applicability of neutral theory to real world communities (Chase 2005;Clark 2012;Rosindell et al 2012), it is now widely accepted that both deterministic and stochastic processes interact to structure species assemblages (Bar-Massada et al 2014;Nuwagaba et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Nuwagaba et al. ; Minoarivelo and Hui ): dAiAidt=fAfalse(xifalse)=rArAkitalicγ(xi,xk)AkKAfalse(xifalse)+jbAiPjwAiPjPj1+hjwAiPjPj dPjPjdt=fPfalse(yjfalse)=rPrPkitalicγ(yj,yk)PkKPfalse(yjfalse)+ibPjAiwPjAiAi1+hiwPjAiAiwhere r is the intrinsic population growth rate, and h the handling time that animals spend for visiting a plant and digesting the nutrients extracted from the plant; both are assumed to be trait‐independent to avoid overparameterization of the model ( r A = r P = 1; h = 0.1). Note that parameter values provided below in brackets are used as reference for sensitivity tests.…”
Section: Methodsmentioning
confidence: 99%